2018
DOI: 10.1002/hep4.1223
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility Group Box‐1 and Liver Disease

Abstract: High‐mobility group box‐1 (HMGB1) is a ubiquitous protein. While initially thought to be simply an architectural protein due to its DNA‐binding ability, evidence from the last decade suggests that HMGB1 is a key protein participating in the pathogenesis of acute liver injury and chronic liver disease. When it is passively released or actively secreted after injury, HMGB1 acts as a damage‐associated molecular pattern that communicates injury and inflammation to neighboring cells by the receptor for advanced gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 175 publications
2
79
0
2
Order By: Relevance
“…Recent study has shown that hepatic inflammation and fibrogenesis are closely associated with hepatocellular necrosis and apoptosis (Lee & Friedman, ). Consistently, it has been well‐documented that danger signals such as high‐mobility group box‐1 and IL‐33 released from dying cells are critical activators in sterile inflammation that enhances the severity of several liver diseases (Gaskell, Ge, & Nieto, ; Neumann, Schiller, & Tiegs, ). Furthermore, proinflammatory cytokines such as IL‐1β and TNF‐α are closely associated with the progression of ALI because antagonizing these cytokines ameliorates the severity of liver damages induced by CCl 4 exposure (Sato et al, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Recent study has shown that hepatic inflammation and fibrogenesis are closely associated with hepatocellular necrosis and apoptosis (Lee & Friedman, ). Consistently, it has been well‐documented that danger signals such as high‐mobility group box‐1 and IL‐33 released from dying cells are critical activators in sterile inflammation that enhances the severity of several liver diseases (Gaskell, Ge, & Nieto, ; Neumann, Schiller, & Tiegs, ). Furthermore, proinflammatory cytokines such as IL‐1β and TNF‐α are closely associated with the progression of ALI because antagonizing these cytokines ameliorates the severity of liver damages induced by CCl 4 exposure (Sato et al, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…In addition it is equally important to investigate either one of the HMGB1 isoform dominates or regulates the activity of other isoforms (Gaskell et al . ) which is essential to elucidate the importance of HMGB1 in epileptogenesis and to design HMGB1 targeted therapies that specifically focus each HMGB1 isoform.…”
Section: Future Perspective Of Hmgb1mentioning
confidence: 99%
“…Moreover, future HMGB1 antagonist should be designed in a way that it would selectively block to harmful disulfide isoform of HMGB1 overcoming the limitation of currently available HMGB1 antagonist which binds to all the three isoforms of HMGB1 ). In addition it is equally important to investigate either one of the HMGB1 isoform dominates or regulates the activity of other isoforms (Gaskell et al 2018) which is essential to elucidate the importance of HMGB1 in epileptogenesis and to design HMGB1 targeted therapies that specifically focus each HMGB1 isoform.…”
Section: Future Perspective Of Hmgb1mentioning
confidence: 99%
“…HMGB1 is a non-histone nuclear protein that facilitates the binding of regulatory proteins to DNA and typically enhances transcriptional activation 10 . When released extracellularly, HMGB1 can binds to one of its receptors, such as RAGE or TLR4 36 . In our previous study, Atg7-/- mice develop hepatic tumors at 9-month old in the liver, which could be inhbited by the deletion of either Hmgb1 or Rage 2 .…”
Section: Resultsmentioning
confidence: 99%